Eficácia de revestimentos de goma arábica incorporados com óleo essencial de Origanum vulgare L. e Rosmarinus officinalis L. no controle da podridão mole em ameixas - Andrade, Sonalle Carolina Albuquerque de (2016)
In this study, the efficacy of coatings comprising gum arabic (GA) and the essential oil from Origanum vulgare L. (OVEO) alone or in combination and Rosmarinus officinalis L. (ROEO) as a postharvest treatment to control Rhizopus soft rot on plums during storage at room temperature (25 °C for 8 days) and cold temperature (12 °C for 21 days) was evaluated. The effects of these coatings on some physicochemical and sensory characteristics of the fruit were also assessed. The minimum inhibitory concentrations (MIC) of OVEO and ROEO were 0.25 μL/mL and 1 μL/mL, respectively. The Fractional Inhibitory Concentration Index of the combined EOs (≤ 0.25) against Rhizopus stolonifer indicated a synergic interaction. The incorporation of a combination of GA and OVEO at 0.25 μL/mL or of GA and OVEO at 0.06 μL/mL plus ROEO at 0.25 μL/mL in the growth media strongly inhibited the mycelial growth, spore germination and sporulation of R. stolonifer. Both the combination of GA + OVEO and GA + OVEO + ROEO delayed the occurrence of soft rot in artificially contaminated plums and decreased the number of infected fruits at the end of storage at room and cold temperatures. GA-OVEO or GA-OVEO-ROEO coatings preserved the postharvest physicochemical quality aspects and enhanced the sensory parameters color and flavor of plums. However, the GA-OVEO coating negatively affected the aftertaste of fruit. Fruit coated with GA-OVEO and GA-OVEO-ROEO exhibited greater amounts of xylose, malic and ellagic acid and rutin at the assessed storage period. These results indicate the coatings comprising GA and OVEO alone or in combination with ROEO as promising postharvest treatments to prevent the Rhizopus soft-rot and preserve the postharvest quality in plums.